Effect of Antioxidant Activity of Ethanol Extract of Leaf of Cajanus indicus Spreng as Hepatoprotective Agent A Novel Role of Free Radical Scavenging Action - Biswajit Majumdar, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Effect of Antioxidant Activity of Ethanol Extract of Leaf of Cajanus indicus Spreng as Hepatoprotective Agent A Novel Role of Free Radical Scavenging Action